IMPACT DU CONFLIT ARME SUR L’ACCENTUATION DE LA PAUVRETE EN CÔTE D’IVOIRE - Yabile, Kinimo René (European Scientific Journal, ESJ, 2013)
Obstacles to development caused by armed conflicts in developing countries are of concern. In Côte D’Ivoire, the political military crisis has resulted in massive displacement of populations, the flight of foreign investors, worsening the unemployment rate combined with the deterioration of living conditions of households. This study examines the impact of the Ivorian armed conflict (2002-2007) on the increase in poverty. Data from two Living Standards Surveys of households conducted before and after the conflict is used by combining the matching method to the double difference. This extension of the classical estimator in difference-difference indicates an overall effect of the conflict estimated to average 26.1%. The simulation analysis (integrating the relevant explanatory variables) enhances the impact of the conflict in 43.14%. The impact of military and political crisis on the rise in poverty could be estimated at 4.75%. The armed conflict has been a major impediment to the development of the Ivory Coast.